Formation of Slivers in the Extended Cross‐Section Platforms of Ni‐Based Single Crystal Superalloy. Issue 9 (7th May 2018) - Huo, Miao; Liu, Lin; Yang, Wenchao; Sun, Dejian; Hu, Songsong; Zhang, Jun; Fu, Hengzhi
Abstract : A model with rejoined platforms is designed to study the casting defects in the platforms of Ni‐based single crystal superalloy. The results of this study indicate the formation of sliver defects in different regions of the platforms. In the platforms, the dendrite deviation started at the section extension region and the misoriented dendrites could continue to grow into the platform to form sliver defects through the competitive growth with the adjacent dendrites. Furthermore, sliver defects formed as a result of the deformation of secondary dendrites induced by the thermal contraction stress based on the polar diagram analysis and the finite element simulation results. Finally, three different factors contributing to the formation of sliver defects in the extended cross‐section platforms are speculated as follows: the orientation of the deformed dendrites, the local thermal field condition, and the sufficient growth space. Abstract : A model has been designed to study the sliver formation in the extended cross‐section platforms for the first time. It is found that the sliver defects appear in different regions of the platforms. The experiment and simulation results indicate that the defects are derived from the continue growing of the deformed secondary dendrites through competitive growth. Three influencing factors might contribute to the formation of sliver defects in the extended cross‐section platforms. On this basis, some measures have been proposed to prevent the formation of slivers.